Tall among the trees: Organizing against globalist forestry in rural British Columbia - Prudham, Scott (Journal of Rural Studies, 2008)
In January of 2001, the TimberWest Corporation permanently closed its Youbou sawmill facility near Duncan, British Columbia, Canada laying off 220 workers. On the surface, the Youbou mill closure reinforced a pervasive sense that workers and communities in the province are increasingly vulnerable to an ever more globally integrated and footloose forest industry. But a funny thing happened in Youbou; the workers fought back. While the mill was completely dismantled and scrapped, with no discernable response from the provincial government, workers from the Youbou sawmill banded together to form a new NGO called the Youbou TimberLess Society. Since its inception, the YTS has developed into one of the most unique and compelling voices for forest policy reform in BC. In so doing, the YTS also represents something of an anomaly in exhibiting many of the characteristics of so-called new social movements, and yet emerging from the industrial working class. This paper explores the ways in which the YTS has served as a powerful arena in which the subjectivities of sawmill workers and other community members have been transformed through organized resistance to global capital. At the same time, informed by the YTS, the paper draws on Polanyi's idea of the dual movement to examine scales and terms on which globalization and competing notions of autonomy are contested in moral economies of both work and nature. Copyright (c) 2008 Elsevier Ltd.
Keywords: Canada; activists; double movement; employees - Canada; forest policy; forest policy - Canada; forest products industry; forests and forestry; lumber industry - British Columbia; lumber industry - Canada; rural studies; social movements; social movements - Canada

In the Zone: Street Markets and Street Merchants in Socio-Legal Perspective - Morales, Alfonso (Conference Papers -- Law & Society, 2008)
Typically when we think of street markets we think of chaotic places full of energy and vibrating with danger and opportunity. Traders or governments create markets to meet existing and emergent demands as well as the unintended consequences of other policy decisions. It is this institutional design, this governance, this regulatory process that provides access to the market and organizes the vending space therein. Public and private entities operating in fiscally constrained environments should attend to the variety of ways there are to establish and regulate markets. Municipalities typically assume that a detailed management scheme is the best approach to managing access to markets and organizing the distribution of space, the assumption being that chaos would result in the absence of the state. However, this is not necessarily the case, merchants' can self-organize access to space as well as a stable and flexible spatial order, and this self-organization can minimize costs, improve access, and contribute to social goods and goals associated with having a public market.This article provides an empirical justification for this claim by examining the creation of Chicago's Maxwell Street Market (hereafter the Market), and describing the subsequent changes in the regulatory scheme of that Market. This discussion recalls Polanyi's observation that all markets are regulated, one way or another, but that the forms and character of regulation obviously varies -- and thus this article argues the thesis that even in apparently unregulated markets we will find regulation, self-created, that produces a social order, in this case a stable and flexible order that accommodates a variety of private and public circumstances and goals. Our case is Chicago's Maxwell St. Market, which between 1973 and 1994 resembled unfettered capitalism. An ethnically heterogeneous multitude of street entrepreneurs organized vending space with little violence in the absence of stable, state sponsored, legal expectations. But this self-organization is nested in an overall history of unregulated street commerce in the area, starting in the 1870s, followed by the City government's creation and regulation of the Market in 1912, then a period of regulation lasting 60 years, followed by a radical change in the regulatory regime that produced a self-organized Market for about 20 years, then finally the City recaptured the Market and has regulated it again since 1994. Planners and policy makers will find this case interesting for three reasons: first, it is an interesting history of public markets and planning interests, second, the data indicate how an ethnically heterogeneous population can self-produce a flexible and stable social order and third, planners and policy makers concerned with locally appropriate and economically efficient, combinations of government and self-regulation of economic activities might apply lessons from this case to the large and growing interest in public markets around the country. ..PAT.-Unpublished Manuscript
Keywords: government regulation; markets; municipal government; nation-state; policy sciences